Best Answer

If the question is to factor the problem, 3x2 - 6x + 9, then it can not be factored.

If the question is to solve for x, assuming the equation is equal to zero, then use the quadratic formula with,

a= 3

b= -6

c= 9

Then, 6 +- sqrt[36 - 4(3)(9)], all divided by 2(3)

6 +- sqrt[36 - 108] divided by 6

[6 +- sqrt(-72)] / 6

To reduce a negative square root, first pull out the negative one by using i, then find the perfect square in 72, which is 36, so the equation becomes:

6+- 6isqrt(2) / 6

Reduce the fraction and cancel the sixes

1 + i sqrt(2) AND 1 - i sqrt(2)

Q: 3xpower of 2-6x plus 9

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(x2 + 26x +) : syntax error.x2 + 26x

.740

8x + 26x - 7 = 34x - 7 = (√34x)2 - (√7)2 = √34x - √7)(√34x + √7)

2(5x - 1)(3x - 2)

The answer to this equation would be 5. This is a math problem.

Related questions

(x2 + 26x +) : syntax error.x2 + 26x

26x + 9 = 699Subtract 9 from each side:26x = 690Divide each side by 26 :x = 690/26 = 26 and 14/690 = 26 and 7/345 = 26.5385 (rounded)

3x2+26x+16 When factorised: (3x+2)(x+8)

x2 + 26x + 48 = (x + 24)(x + 2)

8x2 + 15 + 26x = 8x2 + 26x + 15 = 8x2 + 20x + 6x + 15 = 4x(2x + 5) + 3(2x + 5) = (2x + 5)(4x + 3)

.740

8x + 26x - 7 = 34x - 7 = (√34x)2 - (√7)2 = √34x - √7)(√34x + √7)

x2+36x+120 (x+6)(x+20)

2(5x - 1)(3x - 2)

It is (3x-4)(5x-2) when factored

(5x + 6)(x + 4)

6xsquared minus 26x minus 5 over 3xsquared minus 15x